2008
DOI: 10.1063/1.2996294
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional (2+n) resonance enhanced multiphoton ionization of HCl: Photorupture channels via the FΔ21 Rydberg state and ab initio spectra

Abstract: Mass spectra were recorded for (2+n) resonance enhanced multiphoton ionization (REMPI) of HCl as a function of resonance excitation energy in the 82 600-88 100 cm(-1) region to obtain two-dimensional REMPI data. Analysis of ion-mass signal intensities for excitations via the F (1)Delta(2)(v(')=0-2) and the V (1)Sigma(+)(v(')) states as a function of rotational quantum numbers in the intermediate states either revealed near-resonance interactions or no significant coupling between the F (1)Delta(2) and the V (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(74 citation statements)
references
References 65 publications
(121 reference statements)
2
72
0
Order By: Relevance
“…Both groups investigated the ionization/fragmentation pathways through various vibrational bands of the B 1 Σ + (0 + ) state. Very recently, Kauczok et al [22] have reported similar studies on the singlet and triplet Δ states that previously were identified as being in resonance with selected rovibrational states of the B 1 Σ + (0 + ) state [16][17][18].…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…Both groups investigated the ionization/fragmentation pathways through various vibrational bands of the B 1 Σ + (0 + ) state. Very recently, Kauczok et al [22] have reported similar studies on the singlet and triplet Δ states that previously were identified as being in resonance with selected rovibrational states of the B 1 Σ + (0 + ) state [16][17][18].…”
Section: Introductionmentioning
confidence: 74%
“…The fragmentation ratio (Cl + /HCl + ) does not only show a smooth dependence on the excitation energy, but also crucially depends on the nature of the electronic states as well as on vibrational and rotational quantum numbers [16,18,20]. However, independently of the excitation energy, there exist bands which do not exhibit any significant fragmentation at all.…”
Section: To the Electronic Transitions B[v/e](mentioning
confidence: 99%
See 3 more Smart Citations